Effects of ambient pressure and nozzle diameter on ignition characteristics in diesel spray combustion. (15th April 2021) - Ong, Jiun Cai; Walther, Jens Honore; Xu, Shijie; Zhong, Shenghui; Bai, Xue-Song; Pang, Kar Mun
Highlights: 3-D URANS simulation of diesel spray using Eulerian Stochastic Field method. Ignition characteristics at different ambient densities and nozzle diameters. Ignition site shifts from spray head to periphery as nozzle size increases. Ignition occurs at fuel-rich mixture in high ambient density, large nozzle case. Higher local scalar dissipation rate in large nozzle cases lead to longer IDT. Abstract: Numerical simulations are performed to investigate the effects of ambient density ( ρ am ) and nozzle diameter ( D noz ) on the ignition characteristic of diesel spray combustion under engine-like conditions. A total of nine cases which consist of different ρ am of 14.8, 30.0, and 58.5 kg/m 3 and different D noz of 100, 180, and 363 μ m are considered. The results show that the predicted ignition delay times are in good agreement with measurements. The current results show that the mixture at the spray central region becomes more fuel-rich as D noz increases. This leads to a shift in the high-temperature ignition location from the spray tip towards the spray periphery as D noz increases at ρ am of 14.8 kg/m 3 . At higher ρ am of 30.0 and 58.5 kg/m 3, the ignition locations for all D noz cases occur at the spray periphery due to shorter ignition timing and the overly fuel-rich spray central region. The numerical results show that the first ignition location during the high-temperature ignition occurs at the fuel-rich region at ρ am ⩽ 30.0 kg/m 3 across different D noz . At ρ am = 58.5 kg/m 3, the ignition occurs at the fuel-lean region for the 100 and 180 μ m cases, but at the fuel-rich region for the 363 μ m nozzle case. This distinctive difference in the result at 58.5 kg/m 3 is likely due to the relatively longer ignition delay time in the 363 μ m nozzle case. Furthermore, the longer ignition delay time as D noz increases can be related to the higher local scalar dissipation rate in the large nozzle case.